Updating the criteria for assessing the state of the railway track according to the data of track measuring equipment - B. N. Zenzinov; Y. S. Romen; M. V. Krivolapov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. One of the consequences of the introduction of the Instructions for Assessing the Condition of the Rail Track (enacted on February 28, 2020 No. 436/r) was an increase in the number of newly detected deviations from the norm of track maintenance and their reassignment as malfunctions. As a result, the number of kilometres with limited train speeds has increased by up to 3 times, which may lead to significant losses in transportation and an increase in the cost of the immediate track maintenance.Materials and methods. Data from a special thoroughfare of a diagnostic complex along the operating lines of Russian Railways were used to analyse the actual distribution of types and magnitudes of malfunctions, the number and causes of the speed limits. The authors used computer simulations to determine the dynamic indicators of cars in accordance with the algorithm of the deterministic method for calculating the movement of cars along the railway track.Results. The consequences for assessing the state of the track from the standards specified in Instruction 436/r are analysed. The authors present the results of mathematical modelling of the rolling stock interaction with the track, confirming the feasibility of the proposed changes in the standards: increasing the permissible speeds of passenger trains, assessing the gauge widening in curved sections, clarifying the estimates of unbalanced acceleration.Discussion and conclusion. It is proposed to change a number of standards for assessing deviations from the norms of track maintenance in order to reduce the number of speed limits.